COMPLEXES OF LANTHANIDES(III) BASED ON PHOSPHORYLATED SULFAMIDES: SYNTHESIS AND SPECTRAL INVESTIGATIONS: UDC 546.65+543.42+535.34 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
New complexes with formula Na[LnL14], Ln = La, Nd, Eu, Yb, Lu; HL1=p-NO2(C6H4)S(O)2N(H)P(O)(OCH3)2, were synthesized. Based on the analysis of IR-, NMR spectroscopy data, electronic absorption and diffuse reflection spectra the bidentate coordination mode of L1- via the oxygens of phosphoryl and sulphonyl groups was found. A comparative analysis of the spectral characteristics of the synthesized complexes and previously investigated complexes with general formula Na[Ln(L2)4], HL2=p-CH3(C6H4)S(O)2N(H)P(O)(OCH3)2, was performed.
Keywords: lanthanides, coordination compounds, electronic spectroscopy